Clinical profile of retinoblastoma presenting in a tertiary care hospital, eastern Nepal - Lavaju, Poonam; Badhu, BP; Shah, S; Chaudhary, SK; Upadhyaya, P (Health Renaissance, 2017)
Background: Retinoblastoma is the commonest primary intraocular malignancy of childhood. Under-standing the different modes of presentation with timely intervention are associated with prognosis. Objective: To determine the clinical profile of retinoblastoma and its association with optic nerve infiltration by tumor. Methods: A retrospective analysis of the clinical records and histopathological reports of patients admitted with retinoblastoma in a tertiary heath care center, eastern Nepal (June 2009 to July 2012) was carried out. Results: A total of 27 patients (28 eyes) with retinoblastoma were studied. The mean age at presentation was 2.89 ± 0.93 years. The mean duration of symptoms to presentation was 3.35 month, ranged from 7 days to 2 years. Male to female ratio was 3:2. Thirty-three percent patients were Muslims. Twentyseven patients (96.3%) had unilateral eye involvement. The commonest mode of presentation was leukocoria in 23 eyes (85.2%) followed by redness 9 eyes (33.3%), proptosis in 5 eyes (18.5%) and phthisis bulbi in one eye (3.7%). Histopathological reports of 26 eyes confirmed the diagnosis of retinoblastoma. One patient with distant metastases was referred to oncology center. Infiltration of the optic nerve by tumor cells was seen in five eyes (18.5%); of which two cases had proptosis (p-0.166). At two years follow up, recurrence was seen in one patient with proptosis and optic nerve infiltration (p-0.136). Age at presentation was positively associated with recurrence of tumor (p-0.005). Conclusion: Leucokoria was the most common mode of presentation of retinoblastoma. Larger sample size with longer follow up is required to come to a definite association with optic nerve infiltration by tumor. Health Renaissance 2015;13 (3): 129-136